Project management maturity model: the case in an automotive industry in Brazil - de Souza Scotelano, Laíce; Dalvo Pereira da Conceição, Roberta; da Costa Leonídio, Ueliton; Silva de Jesus, Carlos (Brazilian Journal of Operations & Production Management, 2017)
This study discusses the theoretical concepts related to project management, specifically on the measurement of its implementation, through the concepts of maturity models. Moreover, in order to confirm the theoretical concepts related, it will be presented the results of a survey data conducted in an automotive industry in Brazil (Rio de Janeiro state), through the research of maturity proposed by Darci Prado. This survey will demonstrate the perception of employees at the different areas on the project maturity in this organization. In addition, the result found revealed that the organization analyzed is at the levels observed and calculated, considering the average level of maturity of the region and country. It is concluded that the Brazilian methodology adopted was effective in terms of measuring the level of maturity in a Brazilian organization. It is estimated that this work can contribute to those organizations concerned in the application of project management and that these practices become entrenched and fully disseminated and becoming part of their culture.